2005
DOI: 10.1529/biophysj.104.054049
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Bacterial Motion between Forward and Backward Swimming Caused by the Wall Effect

Abstract: A bacterial cell that has a single polar flagellum alternately repeats forward swimming, in which the flagellum pushes the cell body, and backward swimming, in which the flagellum pulls the cell body. We have reported that the backward swimming speeds of Vibrio alginolyticus are on average greater than the forward swimming speeds. In this study, we quantitatively measured the shape of the trajectory as well as the swimming speed. The trajectory shape in the forward mode was almost straight, whereas that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
61
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 29 publications
8
61
3
Order By: Relevance
“…When the curved cells of Vibrio alginolyticus swim near a planar surface, forwardmoving cells run in a straight line but backward-moving cells run in a curved arc or in circles (176,197). What distinguishes the behavior of forward-and backward-running cells is unknown (197).…”
Section: Side Effects: Motility Near Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…When the curved cells of Vibrio alginolyticus swim near a planar surface, forwardmoving cells run in a straight line but backward-moving cells run in a curved arc or in circles (176,197). What distinguishes the behavior of forward-and backward-running cells is unknown (197).…”
Section: Side Effects: Motility Near Surfacesmentioning
confidence: 99%
“…When the curved cells of Vibrio alginolyticus swim near a planar surface, forwardmoving cells run in a straight line but backward-moving cells run in a curved arc or in circles (176,197). What distinguishes the behavior of forward-and backward-running cells is unknown (197). Once again the surface is "down" relative to the bacterial cell, but in this case, V. alginolyticus swims in large counterclockwise turns, opposite those of E. coli (197), probably because in backward-moving cells the single flagellum leads and pulls the cells.…”
Section: Side Effects: Motility Near Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the published trajectories (7), each reversal typically results in a small change in cell orientation, and thus several reversals appear to be necessary for a significant change in the swimming direction. Backtracking was also observed in a number of single flagellated marine bacteria such as Shewanella putrefaciens, Pseudoalteromonas haloplanktis, and Vibrio alginolyticus, which execute the so-called run-reverse steps when following attractants released from porous beads and from algae (8)(9)(10). A pioneering experiment in V. alginolyticus revealed that the timereversal symmetry in the run and the reverse intervals is broken when the cell swims near a surface.…”
mentioning
confidence: 94%
“…A pioneering experiment in V. alginolyticus revealed that the timereversal symmetry in the run and the reverse intervals is broken when the cell swims near a surface. In such a case, although the forward swimming remains more or less straight, the backward trajectory is remarkably curved and often forms a tight circle a few bacterial lengths in diameter (9). This asymmetry in swimming can be explained by a hydrodynamic interaction with the surface that produces a turning (yawing) moment on the cell body (11).…”
mentioning
confidence: 99%